FORMATION OF INFORMATION LITERACY OF FUTURE TEACHERS OF the UKRAINIAN LANGUAGE AND LITERATURE - Olha О. Lilik (Alfred Nobel University Publisher, 2022)
The article substantiates the need for purposeful formation of information literacy of future teachers of Ukrainian language and literature, as it plays a significant role in shaping the professional competence of future teachers of that subject. It was found that information literacy includes the ability to effectively search and use sources and information, systematize it, the ability to distinguish plagiarism, distinguish facts from judgments, the ability to hypothesize and evaluate alternatives, and adhere to the principles of academic integrity. The features of formation of information literacy of future teachers of Ukrainian language and literature in the context of classroom and extracurricular work on various normative and selective disciplines of general and professional training cycles («Modern children's and adolescent literature», «History of Ukrainian literature», «Methods of teaching Ukrainian language» , "History of the State and Law of Ukraine", "Fundamentals of Academic Integrity") were distinguished. A system of tasks for the formation of information literacy is suggested, in particular: checking the authorship of quotations and proverbial expressions, a quiz about Taras Shevchenko's monuments in the world, searching for images on the Internet and preparing historical or cultural commentaries, recognizing orders and medals through online services of independent Ukraine, creation of posters, videos, infographics, icons on linguistic and literary topics, analysis of scientific publications and their discussion, creation of presentations and drafting codes of honor for students of the academic group. In the context of the study, such forms and methods were used as brainstorming, the tree of assumptions, the ladder of success, cubing, knowledge maps, trainings, with the help of which the formation of information literacy of future teachers of Ukrainian language and literature was achieved. It is noted that the formation of the studied phenomenon was carried out within the framework of non-formal education - in the format of participation of students in the grant program for information media literacy «Information media literacy: learn yourself - teach others» international project «Learn and distinguish: Research and Exchanges" (IREX) with the support of the British and US Embassies in Ukraine in partnership with the Ministry of Education and Science of Ukraine and the Academy of the Ukrainian Press. The results of the participation were presented by students within the "Relay of Champions", as well as presented by teachers in the manual "Guide to information literacy for students and teachers of modern educational institutions: a workshop".